For whom the bells knell. Issue 3 (September 1988) - Heim, M; Steinbach, T
Abstract : A 72-year-old widowed woman known to have an organic brain syndrome was hospitalised owing to gangrene of her lower limbs. The gangrene had been caused by an adduction contracture of her hip resulting in pressure on the medial surface of her left leg. In addition she had pressure sores over both trochanters and the sacrum. The smell of putrefication could be sensed from a distance and on examination large white worms could be seen slithering in the decomposing tissue. The patient was pyrexial, oblivious of her surroundings, and without pain. Surgery--limb amputations--would not restore the patient to a cognitive state nor improve here quality of life, but abstinence posed an inherent threat of sepsis, and revulsion to the attendants. The sacral pressure sore was so large that surgical closure was impossible. The question of surgical intervention is discussed.